Real-world perioperative and long-term oncologic outcomes after standardized thoracoscopy without access incision (TWAI) major pulmonary resections for non-small cell lung cancer: a retrospective cohort of more than 2,000 patients - Seguin-Givelet, Agathe; Lafouasse, Chloé; Mekkar, Akli; Gossot, Dominique; Boddaert, Guillaume (Current Challenges in Thoracic Surgery, 2026)
Following JCOG0802 and CALGB 140503, real-world data are needed to assess long-term oncologic outcomes of segmentectomy beyond randomized settings. This was a single-center retrospective observational cohort study using a prospectively maintained database. The aim was to report real-world perioperative and long-term results of a standardized thoracoscopy without access incision (TWAI) major pulmonary resections fissure-first technique for resectable non-small cell lung cancer (NSCLC).